The Prevalence of HBB Mutations among the Transfusion-Dependent and Non Transfusion-Dependent Hb E/β-Thalassemia Children in a Tertiary Center of West Bengal, India. (4th May 2021) - Saha, Jinia; Panja, Amrita; Nayek, Kaustav
Abstract: Hb E ( HBB : c.79G>A)/β-thalassemia (Hb E/β-thal) is responsible for nearly half of all the different kinds of severe β-thal. This disorder is characterized by a wide range of clinical variability ranging from mild, asymptomatic non transfusion-dependent thalassemia (NTDT) to severe transfusion-dependent thalassemia (TDT). The aim of the present study was to determine the prevalence of different β-globin gene ( HBB ) mutations in Hb E/β-thal subjects and their potential role in transfusion dependence. One hundred and ten consecutive children with Hb E/β-thal attending the Pediatric Department of Burdwan Medical College, Burdwan, West Bengal, India were enrolled. Based on hemoglobin (Hb) electrophoresis or high-performance liquid chromatography (HPLC), patients were recruited and later β-globin gene sequencing was done to find out the prevalence of different HBB mutations. Transfusion-dependent thalassemia was seen in 42 children (38.2%), while NTDT was seen in 68 children (61.8%). A total of 10 different β-globin mutant alleles were characterized. The most frequent mutation on the β-globin gene was IVS-I-5 (G>C) ( HBB : c0.92+5G>C) in both groups. The β-globin gene mutations alone cannot determine transfusion dependence among the Hb E/β-thal patients.